TOWN PLANNING ORGANIZATION OF COASTAL TERRITORIES RIVER ECOSYSTEMS OF THE UKRAINIAN CARPATIES - Mykhailyk, Olha (Collection of scientific papers «ΛΌГOΣ», 2022)
Improving the state of the water area and its coastal territory is a condition for improving the entire river basin, which is the most important forming axis of settlements. The river with its coastal territory, floodplain, coastal meadows, fields, forests is a whole harmoniously connected ecological system - the degradation of one component leads to an imbalance, to the violation of natural ties, to the loss of the integrity of the ecosystem. Development of coastal areas should be balanced, and economic activity should be based on the principles of minimizing the impact on river ecosystems and compliance with current legislation. Urban planning organization of coastal areas should take into account the natural features of river ecosystems of different regions of Ukraine in order to preserve the natural balance. The fast current, the steepness of small river valleys, and the narrow strip of precipitous and dangerous banks of mountain rivers must be taken into account when planning the city-planning organization of comfortable, safe conditions of stay and recreation in the mountainous area of the Carpathians. It is possible to improve the condition of rivers and preserve biodiversity only if balanced management is implemented throughout the river's catchment area.